Effects of phenological stages and ensiling length on chemical composition of Megathyrsus maximus ensiled with Moringa oleifera at different proportions - Damilola Oyaniran; Victoria Olubunmi Ojo; Oludotun Olusegun Adelusi; Temidayo Ayodeji Adeyemi; Ronke Yemisi Aderinboye (Acta Scientiarum. Animal Sciences, 2024)
This experiment investigated effects of phenological stages and ensiling length on chemical composition of Megathyrsus maximus ensiled with Moringa oleifera seeds at different proportions. The grass was harvested at 8 (vegetative stage) and 11 (reproductive stage) weeks after planting and were ensiled with Moringa oleifera seeds at different proportions (100:0, 75:25 and 50:50) for 30, 60, 90 and 120 days. Data collected were analyzed using the 2×3×4 factorial design. Result showed that the CP were significantly lower (P < 0.05) in sole M. maximus silage at both phenological stages for 120 days (70.38 and 63.99 g kg-1) and also in sole M. maximus silage at reproductive stage ensiled for 90 days (68.82 g kg-1). The value of NDF for all proportions decreased with increasing length of ensiling with lowest value at 120 days. The highest tannin content was recorded for 50% M. oleifera seed silage at reproductive stage ensiled for 30 days (4.15 g kg-1). It can be concluded from this study that silages from both phenological stages containing M. oleifera seeds improved chemical composition as the ensiling length prolonged.